Species Identification of Rehabilitated Critically Endangered Orangutans Through DNA Forensic: Implication for Conservation - Christy Lavenia; Dwi Sendi Priyono; Donan Satria Yudha; Tuty Arisuryanti (Tropical Life Sciences Research, 2024)
Rehabilitating and releasing orangutans back into the wild is one of the conservation strategies being pursued to conserve orangutans. However, the species determination between Sumatran, Tapanuli, and Bornean orangutans is essential for reintroduction to avoid outbreeding depression, which could lead to DNA hybridisation and increase the probability of recessive characters. Here, we reported on an investigation of three orangutans in which DNA forensic techniques were used to identify the species before release and reintroduction to their habitat. By applying DNA forensic, the orangutan was successfully confirmed with high probabilities (100%) by identifying two orangutan species, Pongo abelii and Pongo pygmaeus wurmbii. Based on ambiguous morphology, we found the possibility of orangutan species being misidentified in rehabilitation. This case report demonstrates the importance of molecular diagnostics to identify the orangutan species. We also provide workflow recommendations from genetic aspect for rehabilitated orangutans. These recommendations will enable decision-makers to consider genetics when assessing future management decisions, which will help ensure that the orangutan species is effectively conserved.